If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -3) = 3(15 + -1x) Reorder the terms: 6(-3 + x) = 3(15 + -1x) (-3 * 6 + x * 6) = 3(15 + -1x) (-18 + 6x) = 3(15 + -1x) -18 + 6x = (15 * 3 + -1x * 3) -18 + 6x = (45 + -3x) Solving -18 + 6x = 45 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -18 + 6x + 3x = 45 + -3x + 3x Combine like terms: 6x + 3x = 9x -18 + 9x = 45 + -3x + 3x Combine like terms: -3x + 3x = 0 -18 + 9x = 45 + 0 -18 + 9x = 45 Add '18' to each side of the equation. -18 + 18 + 9x = 45 + 18 Combine like terms: -18 + 18 = 0 0 + 9x = 45 + 18 9x = 45 + 18 Combine like terms: 45 + 18 = 63 9x = 63 Divide each side by '9'. x = 7 Simplifying x = 7
| 5x-6=18x-19 | | (4a-4)+(17a+48)=180 | | -6+5X=-36 | | x^2-y=9 | | 3x+3(.65x)=301.50 | | 14x-12-13x=1 | | n+1+(n*0.5)+[37-(2n-4)]=5.50 | | 51405+x+x=301955 | | 4p^2+3p+5=0 | | Y=(14x+b)x | | -27=-10t+3 | | 1000m=1l | | 2x-9+2x-9=50 | | 16r-19=15+18r | | 2x+9+2x-14+x=180 | | 10.6x+84.03=-9.4x+83.45 | | 6+2y-1+36-9=2y+5+36-9 | | 16+14x+10x= | | 6x+20=5x-20 | | 5(2y-3)+7=42 | | 162+x=180 | | 9-y=19 | | -z+12-18=-2z+12 | | 2x+3(x-2)=14 | | 5x+25x-5=6(5x+2) | | 3y-27=21 | | 15-4x=28 | | x^2-40=5x+4 | | 2(7x+14)=56 | | 9c=40 | | -399=7(-8-7n) | | 9x+10=7x+24 |